BREAKING NEWS

## Summary

In mathematics and signal processing, the advanced z-transform is an extension of the z-transform, to incorporate ideal delays that are not multiples of the sampling time. It takes the form

${\displaystyle F(z,m)=\sum _{k=0}^{\infty }f(kT+m)z^{-k}}$

where

• T is the sampling period
• m (the "delay parameter") is a fraction of the sampling period ${\displaystyle [0,T].}$

It is also known as the modified z-transform.

The advanced z-transform is widely applied, for example to accurately model processing delays in digital control.

## Properties

If the delay parameter, m, is considered fixed then all the properties of the z-transform hold for the advanced z-transform.

### Linearity

${\displaystyle {\mathcal {Z}}\left\{\sum _{k=1}^{n}c_{k}f_{k}(t)\right\}=\sum _{k=1}^{n}c_{k}F_{k}(z,m).}$

### Time shift

${\displaystyle {\mathcal {Z}}\left\{u(t-nT)f(t-nT)\right\}=z^{-n}F(z,m).}$

### Damping

${\displaystyle {\mathcal {Z}}\left\{f(t)e^{-a\,t}\right\}=e^{-a\,m}F(e^{a\,T}z,m).}$

### Time multiplication

${\displaystyle {\mathcal {Z}}\left\{t^{y}f(t)\right\}=\left(-Tz{\frac {d}{dz}}+m\right)^{y}F(z,m).}$

### Final value theorem

${\displaystyle \lim _{k\to \infty }f(kT+m)=\lim _{z\to 1}(1-z^{-1})F(z,m).}$

## Example

Consider the following example where ${\displaystyle f(t)=\cos(\omega t)}$:

{\displaystyle {\begin{aligned}F(z,m)&={\mathcal {Z}}\left\{\cos \left(\omega \left(kT+m\right)\right)\right\}\\&={\mathcal {Z}}\left\{\cos(\omega kT)\cos(\omega m)-\sin(\omega kT)\sin(\omega m)\right\}\\&=\cos(\omega m){\mathcal {Z}}\left\{\cos(\omega kT)\right\}-\sin(\omega m){\mathcal {Z}}\left\{\sin(\omega kT)\right\}\\&=\cos(\omega m){\frac {z\left(z-\cos(\omega T)\right)}{z^{2}-2z\cos(\omega T)+1}}-\sin(\omega m){\frac {z\sin(\omega T)}{z^{2}-2z\cos(\omega T)+1}}\\&={\frac {z^{2}\cos(\omega m)-z\cos(\omega (T-m))}{z^{2}-2z\cos(\omega T)+1}}.\end{aligned}}}

If ${\displaystyle m=0}$ then ${\displaystyle F(z,m)}$ reduces to the transform

${\displaystyle F(z,0)={\frac {z^{2}-z\cos(\omega T)}{z^{2}-2z\cos(\omega T)+1}},}$

which is clearly just the z-transform of ${\displaystyle f(t)}$.

## References

• Eliahu Ibraham Jury, Theory and Application of the z-Transform Method, Krieger Pub Co, 1973. ISBN 0-88275-122-0.